Impact of corporate income taxation on capital structure in developing Southeast Asian nations: empirical evidence from Tiger Cub Corporations - Ali Mahgoub, Nuha Kamaleldin (2020)
The increasing investment in the Tiger Cub Nations of Indonesia, Malaysia, Philippines, Thailand, and Vietnam has driven the developing nations towards greater industrialization and to becoming export leaders in the Southeast Asian region. The integration and accelerated growth of their financial markets, in addition to investment incentives to attract foreign direct investment shape a critical environment for corporate and individual investors. While their economies sustain a fiscal policy through the implementation of corporate and personal taxation, this paper aims to highlight the impact of corporate income taxation on the capital structure of firms. Associated with the share of debt in corporate capital, the investigation dissects into the impact of corporate taxation on leverage, while considering capital structure determinants as control factors as proposed by conventional literature. This paper enlists local stock-exchange listed firms and their debt structure during the period 2008-2019, following the global financial crisis and corporate tax reforms in Malaysia.